2013
DOI: 10.1039/c2ob26648b
|View full text |Cite
|
Sign up to set email alerts
|

Dual-action inhibitors of HIF prolyl hydroxylases that induce binding of a second iron ion

Abstract: Inhibition of the hypoxia-inducible factor (HIF) prolyl hydroxylases (PHD or EGLN enzymes) is of interest for the treatment of anemia and ischemia-related diseases. Most PHD inhibitors work by binding to the single ferrous ion and competing with 2-oxoglutarate (2OG) co-substrate for binding at the PHD active site. Non-specific iron chelators also inhibit the PHDs, both in vitro and in cells. We report the identification of dual action PHD inhibitors, which bind to the active site iron and also induce the bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…We performed titrations with Fe( ii ) to investigate whether PHD inhibition involves iron chelation in solution, as for some compounds upregulating HIF-α, e.g. dipyridine (DP) 9 , 75 and likely, desferrioxamine (DFO). 75 , 76 Both HeLa and Hep3b cells were pre-treated with DMSO, DFO, IOX4, FG-4592, GSK1278863, or Molidustat (6 hours), followed by administration of ferrous ammonium citrate (FAC, for 20 hours).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed titrations with Fe( ii ) to investigate whether PHD inhibition involves iron chelation in solution, as for some compounds upregulating HIF-α, e.g. dipyridine (DP) 9 , 75 and likely, desferrioxamine (DFO). 75 , 76 Both HeLa and Hep3b cells were pre-treated with DMSO, DFO, IOX4, FG-4592, GSK1278863, or Molidustat (6 hours), followed by administration of ferrous ammonium citrate (FAC, for 20 hours).…”
Section: Resultsmentioning
confidence: 99%
“…dipyridine (DP) 9 , 75 and likely, desferrioxamine (DFO). 75 , 76 Both HeLa and Hep3b cells were pre-treated with DMSO, DFO, IOX4, FG-4592, GSK1278863, or Molidustat (6 hours), followed by administration of ferrous ammonium citrate (FAC, for 20 hours). With DFO, HIF-1α upregulation is completely abolished by addition of ferrous iron, whereas with the other inhibitors, including DMOG, HIF-1α remained stable on iron addition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further probe into possible mechanisms involved in neuroprotection elicited by D-607 , we carried out a well characterized cell based assay evaluating effects of drug on HIF-1α levels as a surrogate for inhibition of iron-dependent prolyl hydroxylase activity (Callapina et al, 2005; Yeoh et al, 2013). It has been demonstrated that elevation of HIF-1α level as a result of inhibition of PHD prevents neuronal death and provides neuroprotection (Lee et al, 2009; Siddiq et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Nonwovens are highly engineered solutions made up of a variety of materials including fibers, powders, particles, adhesives, films and other materials that provide a multitude of functionalities, for instances, hygienic applications , interlinings , geotextiles , carpet backings , automotive parts , filters , and wipes , etc.…”
Section: Introductionmentioning
confidence: 99%